Capturing stakeholder engagement: CSR and gender equality in global in-house centres - Davidson, Fay; Wreford, John; Penter, Kevan; Perrin, Brian (2017)
© Springer International Publishing AG 2017. Understanding the strategic relevance or significance of Corporate Social Responsibility (CSR) in the international offshore business process outsourcing (OBPO) context requires examination of the complexity of conflicting interests of competing stakeholders, philosophical and theoretical perspectives within the frameworks of different cultures, legal systems and attitudes. This research makes an original contribution to the study of CSR activities of organisations involved in OBPO. The findings could be useful for other researchers in the areas of CSR and compliance, for evaluating or comparing other programs, or used to assist businesses involved in OBPO to target their CSR strategies. This chapter investigates how CSR, particularly the contribution of CSR to gender equity in the workforce, as it is applied and implemented by organisations that engage in OBPO. It contributes to a stream of research that addresses critical success factors for OBPO relating to relationships and end-user customers.